Dislocation strain as the mechanism of phonon scattering at grain boundaries. Issue 3 (26th February 2016) - Kim, Hyun-Sik; Kang, Stephen D.; Tang, Yinglu; Hanus, Riley; Jeffrey Snyder, G.
Abstract : Thermal conductivities of polycrystalline thermoelectric materials are satisfactorily calculated by replacing the commonly used Casimir model (freqeuncy-independent) with grain boundary dislocation strain model (frequency-dependent) of Klemens. It is demonstrated that the grain boundaries are better described as a collection of dislocations rather than perfectly scattering interfaces. Abstract : Thermal conductivities of polycrystalline thermoelectric materials are satisfactorily calculated by replacing the commonly used Casimir model (freqeuncy-independent) with grain boundary dislocation strain model (frequency-dependent) of Klemens. It is demonstrated that the grain boundaries are better described as a collection of dislocations rather than perfectly scattering interfaces.